Salinity Tolerance Mechanism of Economic Halophytes From Physiological to Molecular Hierarchy for Improving Food Quality - Xu, Chongzhi; Tang, Xiaoli; Shao, Hongbo; Wang, Hongyan (Current Genomics, 2016)
Soil salinity is becoming the key constraints factor to agricultural production. Therefore, the plant especially the crops possessing capacities of salt tolerance will be of great economic significance. The adaptation or tolerance of plant to salinity stress involves a series of physiological, metabolic and molecular mechanisms. Halophytes are the kind of organisms which acquire special salt tolerance mechanisms to respond to the salt tress and ensure normal growth and development under saline conditions in their lengthy evolutionary adaptation, so understanding how halophytes respond to salinity stress will provide us with methods and tactics to foster and develop salt resistant varieties of crops. The strategies in physiological and molecular level adopted by halophytes are various including the changes in photosynthetic and transpiration rate, the sequestration of Na+ to extracellular or vacuole, the regulation of stomata aperture and stomatal density, the accumulation and synthesis of the phytohormones as well as the relevant gene expression underlying these physiological traits, such as the stress signal transduction, the regulation of the transcription factors, the activation and expression of the transporter genes, the activation or inhibition of the synthetases and so on. This review focuses on the research advances of the regulating mechanisms in halophytes from physiological to molecular, which render the halophytes tolerance and adaption to salinity stress.
Keywords: Salt tolerance